Outcome of Patients With Prior Stroke/Transient Ischemic Attack and Acute Coronary Syndromes. (April 2020) - Zhang, Dongfeng; Song, Xiantao; Chen, Yalei; Raposeiras-Roubín, Sergio; Abu-Assi, Emad; Henriques, Jose Paulo Simao; D'Ascenzo, Fabrizio; Saucedo, Jorge; González-Juanatey, José Ramón; Wilton, Stephen B.; Kikkert, Wouter J.; Nuñez-Gil, Iván; et al.
The association between prior stroke/transient ischemic attack (TIA) and clinical outcomes in patients with acute coronary syndrome (ACS) has not been well explored. We evaluated the impact of prior stroke/TIA on this specific patient population. We conducted an international multicenter study including 15 401 patients with ACS from the Bleeding Complications in a Multicenter Registry of Patients Discharged With Diagnosis of Acute Coronary Syndrome registry. They were divided into 2 groups: patients with and without prior stroke/TIA. The primary end point was death at 1-year follow-up. Prior stroke/TIA was associated with higher rate of 1-year death (8.7% vs 3.4%; P < .001). It was an independent predictor of 1-year death even after adjustment for confounding variables (odds ratio, 1.705; 95% confidence interval, 1.046-2.778; P = .032). Besides, patients with prior stroke/TIA had significantly increased 1-year reinfarction (5.6% vs 3.8%, P = .015), in-hospital bleeding (8.7% vs 5.8%, P < .001), and 1-year bleeding (5.2% vs 3.0%, P < .001). No difference of antithrombotic therapies or dual antiplatelet therapy (DAPT) types on outcomes was observed in patients with prior stroke/TIA. Prior stroke/TIA was associated with higher 1-year death for patients with ACS who underwent percutaneous coronary intervention. No benefits or harms were observed with different antithrombotic therapies or DAPT types in these patients.